AN IN-DEPTH ANALYSIS OF THE NTPC MARKETING STRATEGY - Rath, S. R.; Kumari, Chandani (ShodhKosh: Journal of Visual and Performing Arts, 2023)
NTPC is India’s largest power utility company. It has been operating its plants at high-efficiency levels. It is not only a power generator but also it is among the great places to work. The company has been ranking in "Top 50 Best Companies to Work for in India" for the past 11 years. Every company has its weaknesses and threats, but it depends on the company how they overcome these issues. We can clearly see that they have big plans for their future, which will make the company more successful.